Organizing knowledge syntheses: A taxonomy of literature reviews - Cooper, Harris M. (Knowledge in Society, 1988)
A taxonomy of literature reviews in education and psychology is presented. The taxonomy categorizes reviews according to: (a) focus; (b) goal; (c) perspective; (d) coverage; (e) organization; and (f) audience. The seven winners of the American Educational Research Association’s Research Review Award are used to illustrate the taxonomy’s categories. Data on the reliability of taxonomy codings when applied by readers is presented. Results of a survey of review authors provides baseline data on how frequently different types of reviews appear in the education and psychology literature. How the taxonomy might help in judging the quality of literature reviews is discussed, along with more general standards for evaluating reviews.
Keywords: American Educational Research Association; Educational Research; General Scholar; Neutral Representation; Research Review